Implementation of the Newest Vital Sign for assessing health literacy in clinical practice: challenges, opportunities, and future directions - Malska, Monika; Major, Katarzyna (Nursing Problems / Problemy Pielęgniarstwa, 2025)
Health literacy (HL) is a crucial factor in improving the quality of healthcare and preventing medical issues. The Newest Vital Sign (NVS) is one of the most commonly used tools for assessing HL, allowing for the rapid identification of patients with limited ability to comprehend medical information. The aim of the study was to evaluate the feasibility of using the NVS tool in clinical practice based on a review of the available literature. The review indicated that the NVS facilitates the adaptation of educational and treatment processes to patients’ individual needs, thereby enhancing the quality of care and clinical communication. However, its implementation poses certain challenges, such as the need for staff training and difficulties related to validation in different languages. Despite these limitations, the NVS remains a promising tool for accurately assessing HL and reducing the risk of medical errors.